Utilizing Blockchain Technology to Ensure the Authenticity of Diplomas - Hasan Wijaya; Adam Sekti Aji (Kirana Publisher (KNPub), 2026)
A diploma management system presently utilized in Indonesia remains a manual, paper-based approach.This system exhibits multiple deficiencies, including diploma forgery, lost diplomas, damaged diplomas,hand-written diplomas, data transparency difficulties, and challenges in diploma verification. A softwareapplication named e-Jazah was created to administer digital diplomas utilizing blockchain technology toresolve these challenges. The construction of this new system seeks to mitigate the issues that emerged inthe prior manual system. Blockchain technology is employed to ensure data integrity. The solution isdesigned to utilize a fundamental characteristic of blockchain technology—its tamper-resistant quality—which protects data integrity from alteration or corruption attempts. The system is decentralized,comprising numerous peers that operate the blockchain network. The blockchain network is constructedusing Hyperledger Fabric technology. Hyperledger Fabric was selected due to its status as a permissionedblockchain and its user-friendly smart contract development features. The system consists of a frontendcomponent serving as the user interface, a backend component linking the frontend to the blockchainnetwork, and the blockchain network itself, with the update aimed at enhancing the UI/UX to improve userexperience. The established system streamlines the fundamental procedure of diploma issuance via itsfunctional specifications. The technology may authenticate diplomas using two methods: the diplomanumber and a PDF document.